2006
DOI: 10.1111/j.1468-3083.2006.01940.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological skin changes in heterozygote carriers of mutations in ABCC6, the gene causing pseudoxanthoma elasticum

Abstract: Even though the number of individuals studied here is small and precludes any hasty generalization, having a single mutation in the ABCC6 gene seems enough to modify dermal elastic fibres. The relevance of performing a skin biopsy to identify heterozygote carriers in the family of a PXE patient remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…It should also be noted that PXE is an autosomal recessive disease, although heterozygous carriers of a mutation in one of the ABCC6 alleles have been suggested to demonstrate subclinical findings in the eyes in terms of angioid streaks and presence of subtle histopathologic changes in the skin without overt cutaneous phenotype (Martin et al , 2007, 2008). The morpholino “knock-down” resulted in 54–81% reduction in abcc6a expression, as determined at the mRNA level.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that PXE is an autosomal recessive disease, although heterozygous carriers of a mutation in one of the ABCC6 alleles have been suggested to demonstrate subclinical findings in the eyes in terms of angioid streaks and presence of subtle histopathologic changes in the skin without overt cutaneous phenotype (Martin et al , 2007, 2008). The morpholino “knock-down” resulted in 54–81% reduction in abcc6a expression, as determined at the mRNA level.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that there are no fully documented reports of PXE in three subsequent generations, refuting the existence of classic Mendelian autosomal dominant inheritance. Obligate heterozygote carriers have essentially normal or very limited clinical phenotype but some cases have been reported to show microscopic changes of mineralization in the elastic fibers (Martin et al , 2007). A recent study has suggested that heterozygous carriers may occasionally have serious manifestations, particularly affecting the eyes (Martin et al , 2008).…”
Section: Phenotypic Spectrum Of Pxementioning
confidence: 99%
“…14 Histopathologic abnormalities were found in skin biopsies from some probably heterozygous first-degree relatives of patients with PXE. 13,34,35 Most frequent abnormalities were increase and fragmentation of elastin, which were found less frequently in controls, but which we consider aspecific for PXE. In some biopsies, calcification of elastic fibers was present, but no clumping was mentioned.…”
Section: Phenotype In Carriers Of Pxementioning
confidence: 99%